Bridge design to eurocodes -- UK implementation : proceedings of the Bridge Design to Eurocodes - UK Implementation Conference held at the Institution of Civil Engineers, London, UK, on 22-23 November 2010 - Denton, Steve, Dr (ICE Pub., 2011)
As of April 2010, Eurocodes replaced British Standards as the principal design standards for bridges in the UK. In support of the transition, the Bridge Design to Eurocodes: UK Implementation conference, brought important background and explanatory information into the public domain.